Surface-Bound Molecular Gradients for the High-Throughput Screening of Cell Responses - Lagunas, Anna; Martínez, Elena; Samitier, Josep (Frontiers in Bioengineering and Biotechnology, 2015)
Chemical gradient surfaces are described as surfaces with a gradually varying composition along their length. Continuous chemical gradients have recently been proposed as alternative to discrete microarrays for the high throughput screening of the effects of ligand concentration in cells. Here we review some of the most recent examples in which gradients have been used to evaluate the effect of a varying ligand concentration in cell adhesion, morphology, growth and differentiation of cells, including some of our recent findings. They show the importance of the organization of ligands at the nanoscale, which is highlighted by abrupt changes in cell behavior at critical concentration thresholds.